Nursery of red tilapia Oreochromis niloticus in a small-scale aquaponics system with different stocking densities - Yani Hadiroseyani; Anita May Sharly; Dadang Shafruddin; Apriana Vinasyiam (Jurnal Akuakultur Indonesia)
Aquaponics is a fish and hydroponic plant-rearing system that utilises fish waste as a plant nutrient. Because water quality can be maintained at an optimal level for fish in the system to enhance farming productivity. This study was conducted to evaluate the effects of fish density on the nursery stage of red tilapia in a small-scale aquaponic system. The study was conducted using a completely randomized design at three levels of stocking density, namely 250 fish/m2, 375 fish/m2, and 500 fish/m2 of red tilapia at an initial size of 6.8 ± 0.35 cm, with 30 net pots of bok choy plant as co-culture. The results that the increase in fish population escalated the productivity of both fish and vegetable in 30 days farming period. The stocking density did not affect fish survival 99 ± 0.82%, 97 ± 1.27%, and 97 ± 0.68%, respectively (p>0.05), but supported a better specific growth rate, namely 3.09 ± 0.30%/day; 3.57 ± 0.23%/day; 4.03 ± 0.04%/day (p<0.05). Interestingly, the smallest coefficient of diversity and lowest feed conversion ratio were obtained at 500 fish/m3, whereas absolute length growth did not differ. Bok choy production increased with fish density, namely 2.82 ± 0.06 kg; 2.88 ± 0.08 kg; 3.17 ± 0.10 kg, respectively (p<0.05). The water quality parameter values were almost identical in all treatments, except for the lowest bacterial abundance gained at stocking density of 500 fish/m3. In conclusion, the aquaponic system can be used to nurseries tilapia seeds at high stocking densities for production efficiency.